Perlindungan Hukum Pemegang Polis BLife Plan MultiPro dari Ketidakpastian Pembayaran Uang Asuransi di Akhir Kontrak - Rahayudin Rahayudin (Pusat Riset dan Inovasi Nasional, 2025)
In the context of Indonesia’s evolving insurance landscape, this study examines the legal protection afforded to policyholders of the BLife Plan MultiPro unit-linked life insurance product against uncertainties in end-of-contract benefit payments. Employing a doctrinal-normative and historical approach, the research analyzes statutory provisions from Law No. 8 of 1999 on Consumer Protection through Law No. 40 of 2014 on Insurance and POJK regulations to evaluate the efficacy of preventive (transparency requirements), corrective (mediation and arbitration), repressive (administrative sanctions), and restorative (insurance guarantee scheme) mechanisms. Integrating Fuller’s internal morality of law, Hart’s open-texture theory, and Knight’s risk-uncertainty distinction, the findings reveal that regulatory evolution has progressively enhanced policyholder protection from 65% under the 1999 framework to 95% under the forthcoming 2028 guarantee scheme yet practical gaps persist in consumer education and claims standardization. The study recommends clarifying policy clauses, streamlining administrative procedures, and enhancing judicial discretion to fortify legal certainty and restore consumer confidence